Kajian Keterkaitan Indikator Penilaian Sustainable Development Goals dengan Penerapan Konsep Kampus Hijau - Wenseslaus Garendy Merciano; BY. Arya Wastunimpuna; Widhi Handayani (Jurnal Serambi Engineering, 2024)
The implementation of the Sustainable Development Goals (SDGs) is a global effort to achieve sustainable development in order to protect the continuity of life, now and in the future. Sustainable campus development is a major concern in the current development, especially in facing the challenges of climate change. This study aims to link the Sustainable Development Goals (SDGs) with the concept of implementing a green campus. This indicator was developed using a literature review method, in relation to the concept of sustainable development and the concept of a green campus. The result of this research is that there is a relationship between the sustainable development goals and the green campus concept, which both focus on developing sustainable infrastructure, water and waste management, developing education and community services, improving health quality and food security, and improving institutions and partnerships. The implementation of the Green Campus Concept has therefore resulted in 5 assessment indicators related to the Sustainable Development Goals, namely Education, Research and Community Service; Campus Infrastructure and Facilities; Water, Energy, Waste and Climate Change Management; Health and Food; and Partnerships and Institutions.